WEB-BASED LIBRARY INFORMATION SYSTEM ( E-PERPUS) USING THE AGILE METHOD AT SMP NEGERI 13 MEDAN - Tasya Syalsabilla; Alda , Muhamad (Cattleya Darmaya Fortuna, 2025)
School libraries play an important role in supporting the educational process and improving student literacy. However, manual library management is still common, including at SMP Negeri 13 Medan. This causes various obstacles such as searching for book and member data, limited access to information outside school hours, and delays in returning books. To overcome these problems, this study developed a web-based library information system (e-Perpus) using the Agile method. The system is designed with the PHP programming language and MySQL database with the laravel framework. The Agile method allows for the development of systems that are flexible and adaptive to user needs. The results of the implementation show that the e-Perpus system is able to improve the operational efficiency of libraries and facilitate access to information for students and school staff.